VALIDASI INSTRUMEN KECEMASAN MATEMATIKA SISWA SEKOLAH DASAR MENGGUNAKAN PEMODELAN RASCH: STUDI DESKRIPTIF KUANTITATIF - Dinda Fadia Az Zahra; Ika Fitri Apriani; Rifqy Muhammad Hamzah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The availability of instruments specifically designed to measure mathematics anxiety in elementary school students is still relatively limited, even though this affective aspect plays an important role in the process and outcomes of learning mathematics. This study aims to develop a mathematics anxiety instrument that aligns with the characteristics of elementary school students while also examining its measurement quality through validity and reliability analyses. The study was conducted using a descriptive quantitative approach involving 32 fourth-grade elementary school students in Tasikmalaya Regency as participants. The development of the instrument refers to four dimensions of mathematics anxiety, namely emotional, cognitive, physiological, and behavioral aspects. The development stages include formulating indicators, drafting statement items, validation by experts, readability testing, and empirical testing of the instrument. The data were analyzed using the Rasch model through the Winsteps application, taking into account item fit indices, reliability, separation, and Cronbach's alpha coefficient. The analysis results indicated that the instrument has met the feasibility criteria in terms of content, construct, and language use. Out of the 30 items tested, 28 items fit the measurement model, while two items required further refinement. In addition, an item reliability of 0.97, person reliability of 0.77, and Cronbach's alpha of 0.80 indicate that the instrument has a good level of consistency. These findings suggest that the developed instrument is suitable for identifying the level of mathematics anxiety in elementary school students. ABSTRAK Ketersediaan instrumen yang secara khusus dirancang untuk mengukur kecemasan matematika pada siswa sekolah dasar masih relatif terbatas, padahal aspek afektif tersebut berperan penting dalam proses dan hasil belajar matematika. Penelitian ini bertujuan menghasilkan instrumen kecemasan matematika yang sesuai dengan karakteristik siswa sekolah dasar sekaligus menguji kualitas pengukurannya melalui analisis validitas dan reliabilitas. Penelitian dilaksanakan dengan pendekatan kuantitatif deskriptif yang melibatkan 32 siswa kelas IV sekolah dasar di Kabupaten Tasikmalaya sebagai partisipan. Penyusunan instrumen mengacu pada empat dimensi kecemasan matematika, yaitu aspek emosional, kognitif, fisiologis, dan perilaku. Tahapan pengembangan meliputi perumusan indikator, penyusunan butir pernyataan, validasi oleh pakar, uji keterbacaan, serta pengujian empiris instrumen. Data dianalisis menggunakan model Rasch melalui aplikasi Winsteps dengan mempertimbangkan indeks kecocokan item, reliabilitas, separation, dan koefisien alpha Cronbach. Hasil analisis menunjukkan bahwa instrumen telah memenuhi kriteria kelayakan dari segi isi, konstruk, dan penggunaan bahasa. Dari 30 item yang diuji, sebanyak 28 item sesuai dengan model pengukuran, sedangkan dua item memerlukan penyempurnaan lebih lanjut. Selain itu, reliabilitas item sebesar 0,97, reliabilitas person sebesar 0,77, dan alpha Cronbach sebesar 0,80 mengindikasikan bahwa instrumen memiliki tingkat konsistensi yang baik. Temuan tersebut menunjukkan bahwa instrumen yang dikembangkan layak digunakan untuk mengidentifikasi tingkat kecemasan matematika pada siswa sekolah dasar.